Konceptualna ilustracja naukowa Fritza Kahna - Leszkowicz, Mateusz (Biuletyn Historii Wychowania, 2023)
The paper outlines the origin, development, applications, and impact of conceptual scientific illustration, developed in the early 20th century by Fritz Kahn, a German gynecologist, publisher and popularizer of science. These illustrations explains how things work via concepts, metaphors and illusion. This is in contrast to the descriptive anatomical and natural illustrations of 19th-century paintings which show what things look like. The article presents the systematics of the main types of illustrations by F. Kahn and reflects on reception thereof.